In memoriam: Elena Vladimirovna Dushechkina (May 1, 1941 – September 21, 2020) - Baran, Henryk (Slavica Revalensia, 2020)
This is an obituary for Prof. Elena Dushechkina of the St. Petersburg State University (formerly an employee of E. Vilde Tallinn Pedagogical Institute), a multifaceted scholar whose fields of expertise included Russian Folklore, Old Russian Literature, 19th-century Russian literature (in particular Nikolai Leskov and Nikolai Nekrasov), and 20th-century Russian culture. Prof. Henryk Baran tells the life story of his deceased longtime friend, listing Elena Dushechkina’s major turning points in her career in the academy and her achievements as a Russian literature expert.